Study on Filipino Driver Reaction Time - Palmiano, Hilario Sean; Carigma, Anjilo; Rosario, Noel; Tumaliuan, Erika Angela (Philippine Engineering Journal, 2020)
Abstract –    Driver perception and brake reaction time (PBRT) is an important parameter in highway design and traffic flow analysis. PBRT can be divided into two main components namely (1) perception time, and (2) braking reaction time. In highway design, it is an important parameter in calculating sight distance for geometric design, to ensure road safety. In traffic flow analysis, specifically in microscopic traffic modeling, car-following models typically involve the specification of driver reaction time to replicate the trajectories of vehicles that travel along the highway. Driver reaction time is determined using two approaches: one is by designing and implementing a field experiment, and the other is by parameter estimation using genetic algorithm of vehicle trajectory data using an assumed car-following model. Result shows that Filipino driver reaction time is approximately 1.6 sec using field observation, and 1.5 using numerical estimation from trajectory data. The paper briefly discusses implication of these values on sight distance determination and its application in microscopic traffic flow analysis.     Keywords—driver reaction time, local driving behavior, perception and braking time, car-following